“Manejo de densidad poblacional en la productividad de la hacienda bananera El Rosal” - Lamilla Abril, Jairon Fernando (2018)
SUMMARY "MANAGEMENT OF POPULATION DENSITY IN THE PRODUCTIVITY OF THE BANANERA HACIENDA EL ROSAL" AUTHOR: Jairon Fernando Lamilla Abril TUTOR: Ing. Agrop. Álvaro Pazmiño Pérez, MsC. The banana is of fundamental importance for the economy of Ecuador. Giving due importance to the banana the second source of income to the state. It constitutes this key element of the Ecuadorian economy. Planting densities in banana crops determine the planting distance to improve the results in terms of productivity and crop management. The proper management of crops depends on maintaining an optimum production and with high yields, one of the most important factors is the population density, the quantity of this element is the yield of the harvest in the banana plantations. The Hacienda El Rosal has its management in the population density per hectare, and for this reason it is intended to develop this work, as well as the techniques to optimize the productivity of the company.